Efforts of the Mahakam Ulu Regency Regional Government in Empowering Small and Medium Enterprises - Muslimin Muslimin; Sri Kamariyah; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: How the Regional Government of Mahakam Ulu Regency Efforts in Empowering Small and Medium Enterprises and What is the socio-economic impact of the community from the empowerment of SMEs. Data Collection Techniques include: Interviews, Observations, Documentation. The research informants were Kadin and staff of the Mahakam Ulu Regency Industry, Trade, and Cooperatives Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study showed. The empowerment program carried out by the Mahakam Ulu Regency Industry, Trade, and Cooperatives Office includes: a. Identify the potential and community empowerment programs in the economic sector. This is done with the development and Human Resources (HR) of the SMEs themselves, b. Coaching for industrial management magazines and improving entrepreneurship and c. Marketing development in an effort to increase market access through improving product quality and product marketing. Improving the quality of SME products accompanied by improving packaging quality, improving hygiene and product certification, and exhibiting small industries. Impact of SME empowerment carried out by the Mahakam Ulu Regency Industry, Trade, and Cooperatives Office: a. The productivity of MSME entrepreneurs shows optimal results. b. The impact of the empowerment of SMEs not only affects job opportunities in the surrounding community but also has an impact on the income of the surrounding community.